2022
DOI: 10.3390/healthcare10091602
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication Patterns during a Pandemic: A Qualitative Study on Romanian Mothers’ Beliefs toward Self-Treatment of Their Children

Abstract: Self-medication represents a significant healthcare and health policy issue worldwide, both in developed and underdeveloped countries. Currently, the COVID-19 pandemic is considered a relevant context that could subtly trigger self-medication behavior because of limited access to health care services and the threat of infection with the SARS-CoV-2 virus. While the previous research conducted with quantitative methodologies reported a dramatically increased rate of self-medication around the world, qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This trend is similar to a study done in Romania which showed fever as the commonest symptom and the antipyretics commonly used by mothers without prescription. 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend is similar to a study done in Romania which showed fever as the commonest symptom and the antipyretics commonly used by mothers without prescription. 12…”
Section: Discussionmentioning
confidence: 99%
“…11 Inadequate medical knowledge, monetary and emotional reasons along with limited and restricted access to healthcare facilities enhanced the avoidance and delayed visits to the healthcare professionals. 12 Medications being made available at people's doorsteps by courier services has contributed to an upsurge in self-medication practices since partial/complete lockdown and social distancing were widely encouraged throughout the pandemic period. 13 Difficulty in approach to professional healthcare services, either due to lack of transport or family beliefs is also a contributory reason for self-medication for common diseases in children.…”
Section: Introductionmentioning
confidence: 99%